(untitled) (Conferencea, 2024)
An external audit is an independent verification of the client’s accounting (financial) statements in order to establish its reliability and compliance of ongoing financial and economic transactions with Uzbek legislation; identifying the reasons that hinder the realization of the company’s potential opportunities and developing recommendations for their elimination. The purpose of this thesis is to describe the assessment of the influence of internal and external factors when conducting a management audit [1].